Histochemical Changes of Ovary in Relation to Pituitary Gland During Prepubertal Period in Goat (Capra hircus) - Nagamalleswari, Y. (Indian Journal of Veterinary Anatomy, 2018)
Goats are not sexually competent at birth and post-natal development of reproductive organs regulated by pituitary hormones play an important role in attainment of puberty and that in turn reflects upon the optimum reproductive performance. The present work is aimed to explore the histochemical changes of ovary in relation to pituitary gland in prepubertal goats. Type II basophils in pituitary gland showed intense PAS positive reaction that increased with age emphasizing the increase in production of LH and FSH from prepubertal to pubertal stage. It is well correlated with lipid localization in granulosa cells, ovum and theca internal cells associated with steroid hormone production and high alkaline phosphatase activity associated with steroid hormone metabolism in ovaries. There was significant increase in acid phosphatase activity in oocytes, zona pellucida and theca interna cells of vesicular and atretic follicles indicating the secretory activity associated with the Golgi complex and lysosomes.